2014
DOI: 10.1177/0022034513519108
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Resolvin D1 Biosynthetic Pathways in Salivary Epithelium

Abstract: Resolvins are potent anti-inflammatory mediators derived from ω-3 fatty acids. Results from our previous studies indicated that resolvin D1 (RvD1) blocks pro-inflammatory responses in salivary glands. Furthermore, RvD1 enhances salivary epithelial integrity, demonstrating its potential use for the restoration of salivary gland function in Sjögren's syndrome (SS). We investigated whether the RvD1 biosynthetic machinery (e.g., cytosolic phospholipase A 2 , calcium-independent phospholipase A 2 , 12/15 and 5-lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…ALX/FPR2 is also expressed in mouse submandibular gland (SMG), and its activation with AT-RvD1 increases a diverse set of intracellular signaling pathways (e.g., intracellular calcium [Ca 2+ ] i , Erk1/2, and Akt) to block TNF-α-mediated caspase-3 activation [14]. We also demonstrated that the machinery for RvD1 biosynthesis and its receptor are expressed and functional in human minor salivary glands (hMSG) with and without SS [15]. The expression levels of ALX/FPR2 seem to be unaltered in hMSG with and without SS [15], indicating that RvD1 could be used as a therapeutic option to treat salivary gland inflammation in SS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALX/FPR2 is also expressed in mouse submandibular gland (SMG), and its activation with AT-RvD1 increases a diverse set of intracellular signaling pathways (e.g., intracellular calcium [Ca 2+ ] i , Erk1/2, and Akt) to block TNF-α-mediated caspase-3 activation [14]. We also demonstrated that the machinery for RvD1 biosynthesis and its receptor are expressed and functional in human minor salivary glands (hMSG) with and without SS [15]. The expression levels of ALX/FPR2 seem to be unaltered in hMSG with and without SS [15], indicating that RvD1 could be used as a therapeutic option to treat salivary gland inflammation in SS patients.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that the machinery for RvD1 biosynthesis and its receptor are expressed and functional in human minor salivary glands (hMSG) with and without SS [15]. The expression levels of ALX/FPR2 seem to be unaltered in hMSG with and without SS [15], indicating that RvD1 could be used as a therapeutic option to treat salivary gland inflammation in SS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Both RvD1 receptors are PTX‐sensitive and do not employ the classical Ca 2+ or cAMP second messengers in PMN cells (Krishnamoorthy et al , ). More recently, however, RvD1 was found to elicit a Ca 2+ response and increase Akt phosphorylation in salivary epithelial cells, suggesting that ALX/FPR2 could activate PI3K pathways in some salivary cells (Leigh et al , ; Nelson et al , ). RvD2 binds to GPR18, also known as DRV2, to activate cAMP signaling (Chiang et al , ).…”
Section: Lipid Mediators Involved In Inflammationmentioning
confidence: 99%
“…RvD1 has recently been of interest for the mitigation of salivary gland inflammation. For example, RvD1 biosynthetic pathways have been discovered in the salivary gland epithelium (Leigh et al , ), and RvD1 blocks cytokine signaling in salivary epithelium to promote cell survival and tissue integrity in rat parotid Par‐C10 cells (Odusanwo et al , ). This was also shown to be true in mouse submandibular gland (SMG) cells coupled with the confirmation of the presence and functionality of the ALX/FPR2 (Nelson et al , ).…”
Section: Lipid Mediators Involved In Inflammationmentioning
confidence: 99%
“…Moreover, RvD1 biosynthetic pathways are expressed and functional in the human and mouse salivary epithelium (Leigh et al. ).…”
Section: Introductionmentioning
confidence: 99%